Use of Platelet‐Rich Plasma in Intra‐Articular Knee Injections for Osteoarthritis: A Systematic Review. Issue 6 (14th February 2015) - Lai, Lawrence P.; Stitik, Todd P.; Foye, Patrick M.; Georgy, John S.; Patibanda, Varun; Chen, Boqing
Abstract: Objective: To systematically analyze the literature on the use of platelet‐rich plasma (PRP) for intra‐articular injections of the knee and its efficacy in the treatment of knee osteoarthritis (OA). Design: Systematic literature reviews were conducted in PubMed, Embase, and CINAHL (ie, Cumulative Index to Nursing and Allied Health Literature) on October 30, 2013, using the keywords "platelet‐rich plasma" and "knee" and "osteoarthritis." Inclusion criteria included (1) studies with human subjects, (2) prospective clinical studies (including either clinical trials or observational studies), and (3) full‐text articles published in English. Exclusion criteria were: (1) animal studies; (2) retrospective studies; (3) patients with previous surgical intervention with total knee arthroplasty or reconstruction of the anterior cruciate ligaments; and (4) articles not published in English Results: A total of 319 abstracts and titles were reviewed (60 from PubMed, 250 from Embase, and 9 from CINAHL). A total of 8 relevant journal articles were identified, all of which were published between 2010 and 2013. One‐half of the studies were prospective observational studies that included only PRP treatment; the rest were prospective comparative studies including both PRP and controls—2 were randomized controlled trials. Of the 4 comparative studies, 3 compared PRP with hyaluronic acid, which was considered as a commonly used effective treatment for knee OA; the other one used saline injection (ie, placebo) as the control. Although most of the analyses suffered from small sample size and was thus inconclusive, the findings consistently indicated that PRP might have better outcomes in patients with a lesser degree of degeneration and in younger patients. Conclusion: PRP intra‐articular injections of the knee may be an effective alternative treatment for knee OA. However, current studies are at best inconclusive regarding the efficacy of the PRP treatment. A large, multicenter randomized trial study is needed to further assess the efficacy of PRP treatment for patients with knee OA.